Optimal design of a skip-lot sampling reinspection plan with a double sampling plan as a reference plan. Issue 3 (3rd July 2021) - Murugeswari, N.; Jeyadurga, P.; Balamurali, S.
Abstract: Skip-lot sampling plans have the provision of inspecting only a fraction of lots, which reduces time and cost of the inspection. Thus, the skip-lot sampling plan is more cost-effective. The intention of this article is to propose the designing methodology to determine the optimal parameters of skip-lot sampling plan of type 2 with a double sampling plan as a reference plan for resubmitted lots by using two points on the operating characteristic curve. Tables summarize the optimal parameters determined under binomial and Poisson distributions for various combinations of producer quality level and consumer quality level by minimizing the average sample number and subject to satisfying both producer's risk and consumer's risk. The execution of the proposed plan is provided with an illustrative example. By comparison, it is proved that the proposed plan is an outstanding plan than the existing skip-lot and conventional sampling plans in terms of probability of acceptance, average sample number, and average total inspection.